2009
DOI: 10.1002/jsfa.3714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium addition on minimally processed leafy vegetables grown in a floating system

Abstract: BACKGROUND: In recent years the consumption of minimally processed leafy vegetables has been increasing. At the same time food quality and its effects on human health have become crucial issues. Since selenium (Se) is an important microelement due to its ability to defend human organisms against free radicals, we investigated the effects of Se on chicory and lettuce production, and assessed the feasibility of a floating system as a method of producing Se-enriched vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 38 publications
8
71
1
2
Order By: Relevance
“…Both the application of Se via the root-zone (in nutrient medium) and in foliar spraying significantly increased concentration of Se in lettuce leaves and roots [28]. Similarly as in the described study it was found that an Se addition (in concentration of 0.5 and 1.0 mg Se dm -3 to the nutrient solution) resulted in an increase in the Se concentration in leaves, which had a positive impact on plant yielding [36]. Increasing Se nutrition has an effect on the concentration of that element in plants [26,37,38].…”
Section: Resultssupporting
confidence: 60%
“…Both the application of Se via the root-zone (in nutrient medium) and in foliar spraying significantly increased concentration of Se in lettuce leaves and roots [28]. Similarly as in the described study it was found that an Se addition (in concentration of 0.5 and 1.0 mg Se dm -3 to the nutrient solution) resulted in an increase in the Se concentration in leaves, which had a positive impact on plant yielding [36]. Increasing Se nutrition has an effect on the concentration of that element in plants [26,37,38].…”
Section: Resultssupporting
confidence: 60%
“…On the other hand, considering alfalfa, chicory and cucumber, the Se concentration levels were comparable. 13,16,20,21,50 However, the larger the Se uptake the greater may be its influence in other nutrient absorption and it may upset the nutritional balance of the plant. Thus, for a better understanding of this influence, the results obtained for the nutrient concentrations were also evaluated by principal components analysis.…”
Section: Minerals Accumulation Pca and Theoretical Calculationsmentioning
confidence: 99%
“…1). Selenium maintained cherry tomatoes, lettuce and chicory quality by suppressing respiration rate and ethylene production at harvest time and during storage (Malorgio et al, 2009;Pezzarossa et al, 2014;Zhu et al, 2017). The lowest respiration rate and ethylene production are desirable to maintain quality and increase shelf life of cherry tomatoes.…”
Section: Fruits Physiology Parametersmentioning
confidence: 99%